2013
DOI: 10.1371/journal.pone.0069337
|View full text |Cite|
|
Sign up to set email alerts
|

Clonal Dynamics of Nasal Staphylococcus aureus and Staphylococcus pseudintermedius in Dog-Owning Household Members. Detection of MSSA ST398

Abstract: The objective of this study was to investigate the dynamics of nasal carriage by Staphylococcus aureus (SA) and Staphylococcus pseudintermedius (SP) among healthy dog-owning household members involved in 7 previous index cases of suspected anthropozoonotic (n = 4) and zoonotic (n = 3) interspecies transmission [4 direct cases, identical SA (n = 3) or SP (n = 1) in owner and dog; three indirect, SP in owner (n = 2) or SA in dog (n = 1)]. Co-carriage with methicillin-resistant coagulase-negative staphylococci (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 50 publications
6
46
1
1
Order By: Relevance
“…Dogs from multi‐dog households were less likely to be positive for mucosal MRS in this study. This finding was unexpected, because sharing of staphylococci, including MRSP, has been reported between in‐contact individuals and pets, particularly in multi‐dog households . Further, females were more likely to carry MDR isolates than males, a finding that disagrees with previous results for MRS .…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Dogs from multi‐dog households were less likely to be positive for mucosal MRS in this study. This finding was unexpected, because sharing of staphylococci, including MRSP, has been reported between in‐contact individuals and pets, particularly in multi‐dog households . Further, females were more likely to carry MDR isolates than males, a finding that disagrees with previous results for MRS .…”
Section: Discussioncontrasting
confidence: 61%
“…Similar risk factors have been reported or proposed for MR S. aureus (MRSA) and MR coagulase negative staphylococci (MR‐CoNS) carriage in humans; the MR‐CoNS population prevalence in healthy dogs is reported to be up to 42% . Carriage may lead to transfer of staphylococci between individuals or to the environment, with long‐term persistence being reported in both circumstances …”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…We did not identify MRSA ST398 (belonging to CC398) in this study, although several cases of ST398 infection in hospitalized patients have been reported in Hong Kong and China (21,22). In recent years, much attention has been focused on the role of pet animals as reservoirs of antimicrobial-resistant bacteria and on the potential transfer of resistance genes from pets to humans (23)(24)(25). A monitoring study of members of dog-owning households in Spain reported cocarriage of S. aureus ST398 in owners and dogs (23), and another investigation in Canada revealed a high prevalence of concurrent MRSA colonization, as well as identifying indistinguishable strains in humans and pet dogs and cats in the same household, suggesting that interspecies transmission of S. aureus and MRSA is possible (24).…”
Section: Discussionmentioning
confidence: 79%
“…In recent years, much attention has been focused on the role of pet animals as reservoirs of antimicrobial-resistant bacteria and on the potential transfer of resistance genes from pets to humans (23)(24)(25). A monitoring study of members of dog-owning households in Spain reported cocarriage of S. aureus ST398 in owners and dogs (23), and another investigation in Canada revealed a high prevalence of concurrent MRSA colonization, as well as identifying indistinguishable strains in humans and pet dogs and cats in the same household, suggesting that interspecies transmission of S. aureus and MRSA is possible (24). A recent review concluded that available data on MRSA transmission between pet animals and humans are limited and that the public health impact of such transmission needs to be subjected to more detailed epidemiological studies (25).…”
Section: Discussionmentioning
confidence: 99%